Social determinants of self-medication with leftover antibiotics in Lebanese households: A cross-sectional study - Reve Khaddaj; Pascale Salameh; Amal Al-Hajje; Julia Bou Dib; Joumana Yeretezian; Michele Cherfane; Reham Kotb; Diana Nakhoul; Reem Awad; Katia Iskandar (PLoS ONE, 2025)
Background Self-medication with leftover antibiotics (LA) is a global health crisis, particularly in contexts of economic and political instability. This study examines the social determinants of health (SDOH) influencing LA use among Lebanese households, focusing on how individuals are born, grow, live, and work. Methods A cross-sectional study was conducted among 368 Lebanese adults to collect data on socio-demographic characteristics, self-medication practices related to LA, and key SDOH such as socioeconomic status (SES), perceived discrimination in medical settings (DMS), political and economic instability, drug shortages, and trusted sources of health information. Data were analyzed using bivariate tests and multivariable logistic regression. Results Bivariate analysis showed that LA use was significantly associated with male gender (45.0% vs. 33.3%, p = 0.024), lower educational levels (58.7% vs. 35.1%, p = 0.002), presence of chronic disease (54.7% vs. 32.2%, p < 0.001), older age (p = 0.028), and a higher household crowding index (p = 0.018). LA use was also more prevalent among participants impacted by political instability, economic crisis, and drug shortages (all p < 0.001). In multivariable logistic regression, chronic disease (OR = 2.711, p = 0.002), economic crisis (OR = 2.013, p < 0.001), and prior experience with the same illness (OR = 4.085, p < 0.001) were identified as significant predictors for LA use. Conclusion These findings show the critical role of socio-economic instability, healthcare access challenges, and experiential factors as key SDOH driving LA practices. The study highlights the urgent need for multi-sectoral interventions addressing economic hardship, improving healthcare access, and enhancing public awareness to mitigate LA misuse and its contribution to antimicrobial resistance in Lebanon.